Proceedings of the 12th International Workshop on Principles of Software Evolution and the 7th Annual ERCIM Workshop on Softwar 2011
DOI: 10.1145/2024445.2024454
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy for software change impact analysis

Abstract: Abstract-Change impact analysis is required for constantly evolving systems to support the comprehension, implementation, and evaluation of changes. A lot of research effort has been spent on this subject over the last twenty years, and many approaches were published likewise. However, there has not been an extensive attempt made to summarize and review published approaches as a base for further research in the area. Therefore, we present the results of a comprehensive investigation of software change impact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 136 publications
(171 reference statements)
0
68
1
Order By: Relevance
“…Lenhert [24] presented a taxonomy of impact analysis methods. Based on a broad literature review, he presents a multitude of criteriaranging from the scope of analysis, the granularity of changes and impact, up to the availability of tool support-to classify and compare various impact analysis approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Lenhert [24] presented a taxonomy of impact analysis methods. Based on a broad literature review, he presents a multitude of criteriaranging from the scope of analysis, the granularity of changes and impact, up to the availability of tool support-to classify and compare various impact analysis approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Lehnert [1] has considered the relationship between dependence clusters and impact analysis and found that clustering can be used to determine the ripple-effect during software maintenance. Beszédes et al [9] looked at the relationship between SEB dependencies, and software maintenance and found that SEB can be used to identify hidden dependencies and thus help in many maintenance tasks, including change propagation and regression testing.…”
Section: Threats To Validitymentioning
confidence: 99%
“…The need to repair and improve software involves a number of challenging tasks such as impact analysis [1], defect detection [2], software reuse [3], [4], and regression testing [5]. Such tasks are facilitated by source code that is easily separated (e.g., loosely coupled).…”
Section: Introductionmentioning
confidence: 99%
“…A taxonomy for impact analysis can be found in [16]. Recent approaches [1,6,8,21] rely on slicing, dependence analysis, dynamic tracing and history mining.…”
Section: Related Workmentioning
confidence: 99%